2011
DOI: 10.1016/j.scienta.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Eggplant relatives as sources of variation for developing new rootstocks: Effects of grafting on eggplant yield and fruit apparent quality and composition

Abstract: ElsevierGisbert Domenech, MC.; Prohens Tomás, J.; Raigón Jiménez, MD.; Stommel, J.; Nuez Viñals, F. (2011). Eggplant relatives as sources of variation for developing new rootstocks: effects of grafting on eggplant yield and fruit apparent quality and composition. Scientia Horticulturae. 128(1): 14-22. doi:10.1016/j.scienta.2010.12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
149
3
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(192 citation statements)
references
References 38 publications
33
149
3
7
Order By: Relevance
“…Some rootstocks of wild species such as wild Solanum are known to emerge slowly and have poor germination (Gisbert et al, 2011). In this study, commercial varieties exhibited high percent germination, but some breeding lines showed lower percent germination.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Some rootstocks of wild species such as wild Solanum are known to emerge slowly and have poor germination (Gisbert et al, 2011). In this study, commercial varieties exhibited high percent germination, but some breeding lines showed lower percent germination.…”
Section: Discussionmentioning
confidence: 64%
“…This can be achieved by using rootstocks that have resistance to soilborne diseases or pests, tolerance to abiotic stress, selective absorption of available nutrients, high vigor and good compatibility with the scion (Davis et al, 2008b;Gisbert et al, 2011;Lee and Oda, 2003;Rivero et al, 2003). In this study, C. annuum commercial rootstocks and breeding lines for rootstock were tested for resistance to Phytophthora blight and bacterial wilt as well as their graft compatibility to commercial pepper cultivars, and have confirmed that the new pepper rootstock is resistant to both Phytophthora blight and bacterial wilt.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations